Comfortable motorcycle helmet. - Wong, Shaw Voon; Salem Hamouda, Abdel Magid; Radin Sohadi, Radin Umar; Megat Ahmad, Megat Mohamad Hamdan; Shuaeib, Farag Mohamed (2008)

(untitled)
The present invention is to provide a helmet having satisfactory compatibility between its shock absorbing capacity, comfortable and satisfying users demand in view of the cost. The invention consist of a motocycle helmet, which uses resilient polymer foam such as expanded polypropylene (EPP). This type of foam recovers its shapes after first impact; therefore provide a protection of head against multi impact hits usually encountered in motocycle crashes. The density configuration to enhance ventilation. The new design shell, which may be of the conventional type or of a new bio-composite material. The said bio-composite shell can be made of reinforced natural fibers such as oil palm, or coca nut, or a combination of one of these fibers with common fibers such as glass, carbon, or polypropylene or the like. The said fiber are impregnanted in either thermoplastics such as polyester or thermoset such as epoxy resins. Therefore this invention relates to a new design of safety helmet, particularly to the one with suitable multi-impact protection, enhanced air ventilation, good fitness, and with an environmental friendly shell material.